Dcf1 regulates neuropeptide expression and maintains energy balance. (22nd May 2017) - Liu, Qiang; Chen, Yu; Li, Qian; Wu, Liang; Wen, Tieqiao
Highlights: Dcf1 gene knockout leads to a decrease in food intake. Dcf1 gene knockout leads to NPY expression downregulation, which in turn affects NPY receptor and GABA level. Dcf1 locates in upstream of NPY, and regulates NPY expression. Dcf1 gene knockout significantly increase ATP concentration, maintaining energy balance. Abstract: Neuropeptide Y (NPY) is an important neurotransmitter in the brain that plays a pivotal role in food intake and energy storage. Although many studies have focused on these functions, the regulation of NPY expression remains unclear. Here we showed that dendritic cell factor 1 (Dcf1) regulates NPY expression and maintains energy balance. We found that NPY expression is significantly reduced in the hypothalamus of Dcf1 knockout (Dcf1 −/−, KO) mice. In contrast, Dcf1 overexpression significantly increases NPY expression in the cell line. We also found that Dcf1 acts upstream of the NPY gene to regulate NPY expression and modulates the NPY-NPY receptor 1-GABA signal. Notably, we observed a significant increase in the ATP concentration in Dcf1 −/− mice, suggesting a greater demand for energy in the absence of Dcf1. We studied the relationship between Dcf1 and NPY and revealed that Dcf1 plays a critical role in energy balance.